MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN SNOWBALL THROWING PADA MATERI SISTEM POLITIK DI INDONESIA KELAS X C SMA NEGERI 3 BANJARMASIN - Ilhamiah, Norbaiti (Lambung Mangkurat University Indonesia, 2014)
Norbaiti, Ilhamiah. 2013. Improving Learning Activities and Learning Achievement of Students through Snowball Throwing Model on Material of Political System in Indonesia at the Students of Class X-C of SMAN 3 Banjarmasin. Sarjanaâs Thesis. Civic Education Department, Social Science, Faculty of Teacher Training and Education, Lambung Mangkurat University, Banjarmasin. The first advisor: Fatimah, the second advisor: Rabiatul Adawiyah.Â Based on pre-research in SMAN 3 Banjarmasin at Class X-C, it was found that the students were less active in teaching and learning activities. Their learning achievements tend to reach the lower point than the expected result. This matter can be seen from the average of the daily test scores which is still below the minimum mastery learning criteria established by the teacher, namely 70. Additionally, the teachers tend to only use lecturing method. The use of the monotonous method will make the students feel bored in following the lesson. The studentsâ boredom can be seen when they frequently do not pay attention to the teacherâs explanation, talk to their friends during the lesson, and when they are passive in question and answer session.This research aims to improve studentsâ activities, studentsâ learning achievement, and to find out the studentsâ responses by using Snowball Throwing method on the material of political system in Indonesia. This research is designed and executed by using the method of classroom action research (CAR). The subject of this research is the students of Class X-C, SMAN 3 Banjarmasin, which consists of thirty-nine students. The techniques of collecting the data are by using test, observation and documentation.The result shows that the learning activities, learning achievement and responses of the students had very good improvement in each cycle. The studentsâ learning activities improved and are included in very good category. Besides, the studentsâ learning achievement also has improved after using Snowball Throwing classically 89,74% and has fulfilled the established minimum mastery learning criteria namely 70 with average 73,33.From the results which indicate the improvement on learning activities, learning achievement, and the responses of the students after implementing Snowball Throwing model, the writer suggests that Snowball Throwing model is not only implemented on civic education learning, but also on other lesson. The writer also suggests that the learning innovation should be done by teachers to improve the quality of teaching and learning process and the learning achievement itself.Â Keywords: Snowball Throwing Model, activities, learning achievement, response